LABOR MARKET TRANSFORMATIONS IN DEVELOPING COUNTRIES (Scientific electronic journal "Labor Economics and Human Capital", 2024)
The article analyzes the current global economic and technological trends affecting the transformation of the labor market and the formation of new socio-economic relations in the context of the formation of the digital economy. The author draws attention to the changes in the nature of labor and forms of labor activity, the requirements for professional skills and abilities. It is shown how the changes associated with the digitalization of the economy directly affect the issues of training and retraining of the most in-demand specialists. Two forecast scenarios for the digital future of the labor market are presented. Excerpts from the latest reports of authoritative international economic organizations and well-known consulting agencies are given.
Keywords: labor relations; labor market; digital economy; robotization; artificial intelligence; personnel development; creation of new jobs; training; retraining.